Consumo alimentar e necessidade energética estimados na deficiência isolada e genética do hormônio de crescimento - Santos, Alécia Josefa Alves Oliveira (2015)
Context: The GH/IGF-I axis has important interactions with the alimentary system and the balance between estimated energy intake (EEI) and estimated energy requirement (EER). Reduced EEI has been described in adult onset acquired GH deficiency, associated to other pituitary deficits. Individuals with isolated growth hormone deficiency (IGHD) due to a homozygous mutation (c.57+1G→A) in the GHRH receptor gene, living in Itabaianinha County in Brazil Northeastern, have abdominal obesity, without insulin resistance. EEI and EER are unknown in this unique cohort. Objectives: To evaluate EEI and EER in this IGHD cohort. Methods: Cross-sectional study of 24 IGHD individuals and 23 adult controls from the same region, matched for age and gender. IEE was evaluated by three food 24-hour recalls and EER by the equation of the Dietary Reference Intakes. Fat mass was assessed by DXA. Results: Both EEI and EER in absolute values were lower in IGHD. However, when corrected by body weight, EEI was higher in IGHD (p=0.005). IGHD individuals consume in percentage more proteins (p<0.0001), less carbohydrates (p=0.013) and equal lipids in comparison to controls. Conclusions: The higher estimated energy intake per body weight indicates a possible increase of orexigenic mechanisms in IGHD individuals, ensuring greater caloric intake, which would have adaptive advantages for small sized individuals, in environment with limited access to food. IGHD individuals seem have a healthier dietary pattern than CO.